Basic facts on civil engineering - Chopra, U.B (Anmol Publications Pvt Ltd, 1994)
The book basic facts civil Engineering especially for the benefit of the students in undergraduate and postgraduate classes. it would be quite useful for all types of readers it gives the meaning words in a simple and comprehensive manner.